PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBINA AKHLAK PESERTA DIDIK DI ERA SOCIETY 5.0 - Al Hamdany, Muhammad Zuljalal; Rahmadani, Ervi; Yuniar, Vira; K, Nurdin (Institut Agama Islam Negeri (IAIN) Bone, 2024)
The main aim and focus of this research is the role of Islamic Religious Education teachers in dealing with the impact of online games on students' morals in the era of society 5.0 at UPT SMP Negeri 4 Masamba. This research uses a type of qualitative research that describes things or data obtained from the field. The subjects in this research were school principals, Islamic Religious Education teachers and students at SMP Negeri 4 Masamba. The data collection techniques used in this research are observation, interviews and documentation. The results of this research are that the use of technology has a more negative impact on students' morals, for example, showing an indifferent and impolite attitude towards others. The efforts made by PAI teachers to develop students' morals are teaching about mahmudah and mazmumah morals, giving punishments that only aim to train students' behavior and morals. Factors that support the moral development of students are the presence of ROHIS, a moral school culture and good synergy between teachers. The inhibiting factors are the lack of good manners among students and the lack of parental supervision of their children when they access the Mobile Legend (ML) application, so that students are more easily affected by the negative impact of online games.